2020
DOI: 10.18510/hssr.2020.8525
|View full text |Cite
|
Sign up to set email alerts
|

Ict in Open and Distance Education: A Tool for Learner Support Services and Policy Development

Abstract: Purpose of the study: The purpose of this study is to highlight the role of Information and Communication Technology (ICT) in open and distance learning system of education at Uttarakhand Open University. This paper also highlights the best practices of ICT in learner support services offered by the University and areas of distinctiveness in utilizing ICT applications. Methodology: This study is a descriptive-analytical in nature and adopts a case-study approach in presenting the various ICT facilities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Khusniati (2014) and Sanjaya, Suartama, Suastika, Sukadi and Dewantara (2021) suggested that the science learning model based on local wisdom can be carried out through the reconstruction of original science (indigenous science) into Western science or scientific science. This learning model makes it easier for students to understand the material because it is contextual and meaningful (Singh & Datt, 2020). Subagia and Wiratma (2009) evaluated the application of the tri pramana-based learning cycle model in chemistry learning in high schools.…”
Section: Introductionmentioning
confidence: 99%
“…Khusniati (2014) and Sanjaya, Suartama, Suastika, Sukadi and Dewantara (2021) suggested that the science learning model based on local wisdom can be carried out through the reconstruction of original science (indigenous science) into Western science or scientific science. This learning model makes it easier for students to understand the material because it is contextual and meaningful (Singh & Datt, 2020). Subagia and Wiratma (2009) evaluated the application of the tri pramana-based learning cycle model in chemistry learning in high schools.…”
Section: Introductionmentioning
confidence: 99%
“…Pedagogical research shows that the Internet can be productively using in the practice of teaching students to formulate research problems and tasks [2,4], organize reflexive activity in understanding the importance of cognitive products, understanding the goals and values of research [1,2]. The ways of organizing the choice of technological elements of research [9], construction and implementation of search strategies [10] are known.…”
Section: Introductionmentioning
confidence: 99%